Isolation, Molecular Detection and Multidrug-Resistant Major Coagulase-Positive Staphylococci from Recurrent Canine Pyoderma - Shobha, Khambam; Ghodasara, Sanjay N; Barad, Dilip B; Javia, Bhavesh B; Yeptho, Atokali H (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Bacterial pyoderma is one of the most frequent skin diseases in dogs. Recurrent pyoderma is often secondary to an underlying skin disease and  is most commonly caused by coagulase-positive staphylococci. The main objectives of this study was to assess the level of resistance acquired by  the most common bacteria responsible for causing recurrent pyoderma in dogs. The methodologies used were molecular methods, minimum  inhibitory concentration, and antibiotic sensitivity testing to study resistance among the isolated bacteria. A total of 80 samples were collected  from the dogs affected with different types of canine pyoderma, presented to the Veterinary Clinical Complex of the College in Junagadh (Gujarat,  India). Of these, 9 (11.25%) dogs were diagnosed with recurrent canine pyoderma. From these 9 cases, 7 (77.78%) isolates were confirmed as  coagulase-positive Staphylococcus comprising, 5 (71.42%) S. pseudintermedius and 2 (28.58%) S. schleiferi subsp. coagulans. Among the 7 major  CoPS isolates, a higher percentage of antibiotic resistance was shown against penicillin-G, followed by amoxyclav and amikacin, and 3 (42.86%)  isolates showed multidrug resistance among selected antibiotics of different classes, and one (14.28%) isolate of S. schleiferi subsp. coagulans showed methicillin-resistant (MRSS) phenotypically by disc diffusion method. These findings highlight the need for periodic assessment of  pathogens and drug susceptibility patterns in different areas to ensure judicious use of antibiotics.
Keywords: Antibiotic resistance, Multidrug resistance, Recurrent canine pyoderma, Staphylococcus schleiferi subsp. coagulans